PENGARUH SELF ASSESSMENT SYSTEM PEMERIKSAAN PAJAK DAN PENAGIHAN PAJAK TERHADAP PENERIMAAN PAJAK - Nursanti, Anita (Pusat Penerbitan dan Publikasi Ilmiah FEB-UMI, 2024)
This study aims to analyze the Influence of Self-assessment System, Tax Audit and Tax Collection on Tax Revenue. Case Study at KPP Pratama South Makassar. The population of this study is taxpayers registered at the South Makassar Tax Service Office, totaling 96,811 taxpayers. In selecting samples, the researcher used the Slovion formula so that the number of samples in this study was 100 samples. results of the analysis show that the variables Self assessment system, Tax Audit and Tax Collection have a positive and significant effect on the Tax Revenue variable